Building in Wetlands to Meet the Housing Demand and Urban Growth in Harare - Sithole Angeline; Goredema Byron (Center for Promoting Ideas (CPI), 2023)
The research assesses the challenges of building in wetlands to meet housing demand. The City of Harare has been in the limelight owing to the reclamation of wetlands for urban development as a remedy to rapid urbanization. There is an increase in the number of people living in wetlands and the inhabitants of wetlands encounter a number of problems that include structural failure of their housing units and they are prone to waterborne diseases. The research recommends that the government and local authorities increase residential development in satellite towns to avoid reclamation of wetlands, and wetlands have to be restored and rehabilitated. There is need to develop effective urban policies and plans concerned with protection and restoration of wetlands. Consultation and participation of all the relevant stakeholders must be treated as a matter of urgency before the utilization of wetlands. Essentially wetlands need to be strictly reserved for recreational purposes.